(Re)visualizing Black lesbian lives, (trans)masculinity, and township space in the documentary work of Zanele Muholi. Issue 2 (3rd April 2017) - Imma, Z'étoile
ABSTRACT: This article explores the politics of representing Black queer and trans subjectivities in the recent documentary film and photography of South African lesbian visual activist Zanele Muholi. While Muholi's work has been most often been positioned as an artistic response to the hate-crimes and violence perpetuated against Black lesbians in South African townships, most notably acts of sexual violence known increasingly as corrective rape, I argue that Muholi's documentary texts trouble the spatial, gendered, and highly racialized articulations that make up an increasingly global corrective rape discourse. The article considers how her visual texts foreground and (re)visualize Black queer and trans gender experiences that relocate, challenge, collaborate with, and at times, perform, masculinity as means to subvert heterosexist and racist constructions of township space and the Black gendered body.